The ASTA model: Integrating lontar taru pramana in environmental learning at elementary schools - Sedana, I Made; Ayu, Putu Eka Sastrika (Journal of Environment and Sustainability Education, 2026)
This study develops and evaluates the ASTA Model an integrative approach combining religious values, science, and Lontar Taru Pramana to strengthen environmental education in elementary schools, addressing the limited use of local wisdom, the absence of holistic pedagogical models, and low environmental awareness among students. This study employed a Research and Development (R&D) design using the 4-D model (Define, Design, Develop, and Disseminate), involving education experts, subject matter experts, teachers, and elementary students as participants in the model development process. The findings indicate that the ASTA Model is conceptually sound, practical for classroom use, and contributes meaningfully to strengthening students’ environmental attitudes. Expert reviews confirmed the model’s content relevance, while classroom implementation showed that both teachers and students could engage with it effectively. The model fostered greater ecological awareness, a stronger sense of responsibility, and more active participation in environmental activities. Integrating the spiritual and ecological values of the Lontar Taru Pramana enriched science learning by strengthening not only students’ cognitive understanding but also their moral and emotional commitment to sustainability. Overall, the ASTA Model provides a novel contribution to both educational theory and practice by integrating spiritual values, scientific concepts, and local wisdom into environmental learning in primary schools. This approach strengthens sustainability education and supports the achievement of SDG 4 (Quality Education) and SDG 13 (Climate Action).